CDR mining and analysis system - Chamboko, Henkel (Midlands State University, 2020)
The purpose of this research was to build an Information System based solution which would help address challenges of slow CDR requests, inaccurate response to requests, workload of data mining procedures and the risks associated with connecting manually to live database exposing live database to risks. CDR mining and analysis system is an electronic data mining and analysis system which is intranet based for security reasons. This system was developed to address risks (preventing write aces to the live database) that are associated with manually connecting to the live billing database to extract Call Detail Records (information relating to an individual) and at the same time reducing work load on the IT team of Tel-One and letting them focus their attention on other important tasks. The system enables authorized users from the relevant departments to be able to conduct CDR mining and analysis from their relevant department and have their results displayed for their use pronto by emailing function which encrypts the data as pdf and sends it as an attachment. The system was also developed for use to react to external customers known as subscriber to react to their itemized bill request as well as create a summary explanation for the result produced to ensure that the request answers exactly what the user requested. The researcher carried out a thorough research of the problems mentioned above using fact finding methodologies. The researcher used interview, observations and questionnaires to research the project. After analyzing the gathered information the researcher developed the CDR mining and analysis system by implementing system development tools namely PHP programming Language Java Scripting (JS) and Mercury Mail for sending email, MySQL data base for storing the data Dreamweaver for integrated development environment and apache which supplied a web server for handling http protocol connections over the internet.